Dynamical chiral symmetry breaking: the fermionic gap equation with dynamical gluon mass and confinement - Capdevilla Roldan, Rodolfo Maia [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
Alguns aspectos da quebra de simetria quiral para quarks na representação fundamental são discutidos no contexto das equações de Schwinger-Dyson. Estudamos a equação de gap fermionica incluindo o efeito de uma massa dinêmica para os gluons. Ao estudar esta equação de gap verificamos que a intenção não é forte o suficiente para gerar uma massa dinâmica dos quarks compatível com os dados experimentais. Também discutimos como a introdução de um propagador confinante pode mudar este cenário, exatamente como foi proposto por Cornwall [1] recentemente, desta forma estudamos uma equação de gap completa, composta pela troca de um gluon massivo e por um termo confinante; M('p POT 2') = 'M IND. c('p POT 2') + 'M IND. 1g'('p POT 2'). Encontramos soluções assintótica desta equação de gap nos casos de constante de acoplamento constante e corredora. Este último caso corresponde a um aprimoramento do cálculo com constante de acoplamento constante feito por Doff, Machado e Natale [2]

Some aspects of chiral symmetry breaking for quarks in the fundamental representation are discussed in the framework of the Schwinger-Dyson equations. We study the fermionic gap equation including effects of dynamical gluon mass. Studying the bifurcation equation of this gap equation we verify that the interaction is not strong enough to generate a satisfactory dynamical quark mass. We also discuss how the introduction of a confining propagator may change this scenario as recently pointed out by Cornwall [1], so we study a complete gap equation composed by the one-dressed-gluon exchange term and a confining term: M('p POT 2') = 'M IND. c('p POT 2') + 'M IND. 1g'('p POT 2'). We find asymptotic solutions for this gap equation in the cases of constant coupling and running coupling constant. This last case is an improvement of the constant coupling calculation of Doff, Machado and Natale [2]
Keywords: Cromodinamica quantica; Partículas (Física nuclear); Quantum chromodynamics